STORYTELLING USING RECONSTRUCTED INDONESIAN FOLKTALES IN ENGLISH TRANSLATION TO IMPROVE THE READING SKILL OF PRIMARY 2 STUDENTS IN SCHOOL X - Ingenies Wijanarko (Magister Teknologi Pendidikan Fakultas Ilmu Pendidikan, Universitas Pelita Harapan, 2021)
Folktales are stories originating in people’s culture, typically passed on by word of mouth before writing systems were developed. It has been known that children stories are never simple stories. The stories generally contain edifying elements and moral lesson to educate children and shape their characters. These elements are even stronger in folktales as they are potential medium to carry moral education from generation to generation. Unfortunately, not all of them contain teachings that are relevant to today’s values and even contain teachings that have unconstructive values. This study used reconstructed folktalesNilam Kandungas the purposes of this study were: (1) to describe the use and implementation of storytelling using Indonesian folktales in order to improve English reading skill towards English comprehension text, vocabulary and fluency of primary 2 students, (2) to analyze primary 2 students’ reading comprehension, vocabulary and fluency as they engaged in reading the Indonesian folktales through storytelling method, (3) to identify problems and obstacles that happened during the implementation process. The subjects of this study are Primary 2 students consist of 26 students. The research used classroom action research design and the instruments are tests.The results showed that (1) students’ vocabulary, comprehension and fluency as parts in reading skills are enhanced, (2) students’ sense of moral education is enhanced (3) storytelling using Indonesian folktales is attractive to students in reading English texts.BAHASA INDONESIA ABSTRACT: Cerita rakyat adalah cerita asli dalam kebudayaan, biasanya diteruskan dari mulut ke mulut sebelum sistem menulis dikembangkan. Sudah sejak dahulu diketahui bahwa cerita anak-anak tidaklah pernah cerita yang sederhana. Cerita-cerita tersebut pada umumnya mengandung unsur-unsur yang dapat mempengaruhi pikiran dan pelajaran moral untuk mendidik dan membentuk karakter. Unsur-unsur ini bahkan lebih kuat di dalam cerita rakyat karena cerita rakyat adalah perantara yang berpotensi untuk membawa pendidikan moral dari generasi ke generasi. Sayangnya, tidak semuanya mengandung pengajaran yang masih relevan dengan nilai-nilai kini dan bahkan mengandung pengajaran yang memiliki nilai-nilai yang bersifat tidak membangun.Studi ini menggunakan cerita rakyat terkonstruksi ulang Nilam Kandungkarena tujuan dari studi ini adalah: (1) mendeskripsikan penggunaan dan penerapan bercerita menggunakan cerita rakyat Indonesia untuk meningkatkan kemampuan membaca Bahasa Inggris dalam memahami bacaan, perbendaharaan kata dan kelancaran membaca dalam Bahasa Inggris siswa kelas 2, (2) menganalisa kemampuan membaca bahasa Inggris siswa kelas 2 ketika mereka sedang terlibat dalam membaca cerita rakyat Indonesia melalui metode bercerita, (3) mengidentifikasikan masalah dan rintangan-rintangan yang terjadi selama proses pelaksanaan.Subjek dari studi ini adalah siswa kelas 2 yang terdiri dari 26 siswa. Penelitian ini menggunakan rancangan penelitian tindakan kelas. Hasil penelitian menunjukkan bahwa (1) keterampilan membaca siswa perbendaharaan kata, memahami bacaan dan kelancaran membaca meningkat, (2) pendidikan moral siswa meningkat(3) bercerita dengan menggunakan cerita rakyat Indonesia lebih menarik bagi siswa dalam membaca teks Bahasa Inggris.